Implementasi Range Of Motion (ROM) Pasif Untuk Meningkatkan Mobilitas Fisik Pada Pasien Dengan Stroke Hemoragik Di Rumah Sakit Vita Insani Pematangsiantar - Sinaga, Veni Delita; Mangara, Azis (Green Publisher Indonesia, 2024)
Stroke is a functional brain disorder in the form of death of neurological nerve cells due to disruption of blood flow in one part of the brain. Hemorrhagic stroke is a ruptured blood vessel in the brain which results in intracranial bleeding. The prevalence of stroke cases every year is 13.7 million and around 5.5 million deaths occur due to stroke. One of the nursing problems that arises in cases of hemorrhagic stroke is impaired physical mobility. Efforts that can be made to overcome physical mobility disorders are passive range of motion (ROM). This research design uses the Case Study method. The sampling method used is purposive sampling. The samples taken were 2 respondents, namely patients with hemorrhagic stroke who were hospitalized at Vita Insani Hospital, Pematangsiantar. The results showed that there was an increase in mobility experienced by hemorrhagic stroke patients, a decrease in muscle strength, Mr. U scales (3) to (4) and in Mr. S scales (2) to (3). Passive range of motion (ROM) is effective in cases of hemorrhagic stroke in increasing physical mobility. Nurses are expected to be able to accompany patients to apply passive range of motion (ROM) in an effort to increase physical mobility in hemorrhagic stroke patients.